Biological quality of drilled well water around the shrimp paste production place in Jor Village, East Lombok District - Dini Yuliansari; Enida Fatmalia; Wahyudin Wahyudin (Jurnal Pijar Mipa, 2023)
This study aimed to determine the quality of dug well water around the shrimp paste production site in Jor Hamlet, Jor Village, Jerowaru District, East Lombok Regency. The type of research used is an experiment with two parameters based on Minister of Health Regulation Number 32 of 2017, namely Biological Parameters, including Coliform and Escherichia coli. The sampling points in this study consisted of three water sampling points from residents' dug wells with two repetitions of sampling in Jor Hamlet, Jor Village, East Lombok Regency, and with consideration of sampling points based on the distance of the dug well to the location of making shrimp paste in below 10 meters and the shrimp paste production site does not have a good wastewater disposal system. Water quality around the shrimp paste production site in Jor Hamlet, Jor Village, Jerowaru District, East Lombok Regency, several parameters do not meet the requirements based on Minister of Health Regulation Number 32 of 2017 concerning Environmental Health Quality Standards and Water Health Requirements for Sanitation Hygiene, Swimming Pools, Solus Per Aqua, and Public Baths, namely Coliform Parameters, samples at sampling points A and B exceed the Quality Standard, namely 230 in both repetitions, while the Maximum Quality Standard is 50 MPN/100 ml. The Escherichia coli Parameters for all samples at all sampling points meet the Quality Standards, namely 0 MPN/100 ml samples, or there may not be Escherichia coli in clean water intended for Sanitary Hygiene. The highest research results for Coliform and Escherichia coli parameters were high at several points due to the distance between the well and the shrimp paste production site, which was very close, and the shrimp paste production site did not yet have a good wastewater disposal system.